Antimicrobial Regimens Prescribed by Canadian Physicians for Chemotherapy-Induced Febrile Neutropenic Episodes - Michel Laverdière; Eric J Bow; Coleman Rotstein; Stratis Ioannou; Danielle Carr; Narguess Moghaddam; the Canadian Fluconazole Study Group (Canadian Journal of Infectious Diseases)
OBJECTIVE: To study the antimicrobial management of cancer patients with chemotherapy-induced neutropenia by Canadian physicians.